2017
DOI: 10.1016/j.cell.2017.08.044
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Interactome Reveals the Protein Organization of the Algal CO2-Concentrating Mechanism

Abstract: SUMMARY Approximately one-third of global CO2 fixation is performed by eukaryotic algae. Nearly all algae enhance their carbon assimilation by operating a CO2-concentrating mechanism (CCM) built around an organelle called the pyrenoid, whose protein composition is largely unknown. Here, we developed tools in the model alga Chlamydomonas reinhardtii to determine the localizations of 135 candidate CCM proteins, and physical interactors of 38 of these proteins. Our data reveal the identity of 89 pyrenoid proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
380
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(399 citation statements)
references
References 67 publications
(102 reference statements)
15
380
2
2
Order By: Relevance
“…Two further low CO 2 ‐inducible proteins (LCIB, LCIC) are present in the same cluster. Recent studies revealed that LCIB and LCIC interact with each other and presumably form a chloroplast‐localized complex (Mackinder et al ., ). In addition, several proteins related to general or oxidative stress can be observed in the LHCSR3‐CRX and FNR clusters (ClpB, BIP1, PRX4, HSP70B, HSP70C, HSP90B).…”
Section: Resultsmentioning
confidence: 97%
“…Two further low CO 2 ‐inducible proteins (LCIB, LCIC) are present in the same cluster. Recent studies revealed that LCIB and LCIC interact with each other and presumably form a chloroplast‐localized complex (Mackinder et al ., ). In addition, several proteins related to general or oxidative stress can be observed in the LHCSR3‐CRX and FNR clusters (ClpB, BIP1, PRX4, HSP70B, HSP70C, HSP90B).…”
Section: Resultsmentioning
confidence: 97%
“…In addition, PSII activity has been initially described to be restricted to stromal thylakoids (McKay and Gibbs ). However, very recently, the presence of both intrinsic and extrinsic PSII subunits in the pyrenoid of the green alga C. reinhardtii has been reported (Mackinder et al , Zhan et al ), including the localization of the PsbQ extrinsic component of PSII in intrapyrenoid thylakoids (Mackinder et al ). Thus, the presence of the PSII extrinsic PSBV subunit (Cc 550 ) in this compartment could not be totally unexpected.…”
Section: Resultsmentioning
confidence: 99%
“…Components of the photosystem I (PSI) complex have also been found in pyrenoids, indicating that intrapyrenoid thylakoids could supply ATP to this compartment via cyclic electron transport, thus covering the energetic demands of carbon fixation at the same time as avoiding the evolution of inhibitory O 2 (McKay and Gibbs , Meyer and Griffiths ). Consequently, it was generally accepted that intrapyrenoid thylakoids are enriched in PSI and lack PSII, although in the green alga Chlamydomonas reinhardtii , the presence of PSII components has been recently reported (Mackinder et al ). However, the presence in this space of either the soluble photosynthetic cytochrome c 6 (Cc 6 ) or the Cc 550 , has not been yet addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, reducing CO 2 flue gas emissions to control global warming is a crucial task (Zhou et al, 2018). Microalgae contributes to approximately one-third of the global CO 2 fixation because of their substantial growth rate (Mackinder et al, 2017;Rosenzweig et al, 2017). Using CO 2 from flue gases as a carbon source to cultivate microalgae is one alternative method for reducing flue gas emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In the first process, HCO À 3 sequentially passes through the plasma membrane, the chloroplast envelope and then the thylakoid membrane, finally arriving at the thylakoid lumen where it is catalysed to CO 2 . CO 2 is next fixed by the RubisCO enzyme (Amc et al, 2017) and then channelled into the Calvin cycle (Spalding, 2008;Mackinder et al, 2017;Hwangbo et al, 2018). In the second process, HCO À 3 in the periplasmic space is converted by carbonic anhydrase into CO 2 , which then diffuses to the stroma and is captured by RubisCO.…”
Section: Introductionmentioning
confidence: 99%